А. Құнанбаевтың «Шоқпардай кекілі бар камыс құлақ» өлеңін 6 сыныпта оқыту жолдары - Есенғазы, А.А. (My University, 2013)
This article describes the technology education in grades 6, Abay poem with innovative learning technologies, based on the works of scholars of linguistics linguists Kazakhs.